Consensus statement: Using laryngeal electromyography for the diagnosis and treatment of vocal cord paralysis. Issue 6 (9th April 2016) - Munin, Michael C.; Heman‐Ackah, Yolanda D.; Rosen, Clark A.; Sulica, Lucian; Maronian, Nicole; Mandel, Steven; Carey, Bridget T.; Craig, Earl; Gronseth, Gary
ABSTRACT: Introduction: The purpose of this study was to develop an evidence‐based consensus statement regarding use of laryngeal electromyography (LEMG) for diagnosis and treatment of vocal fold paralysis after recurrent laryngeal neuropathy (RLN). Methods: Two questions regarding LEMG were analyzed: (1) Does LEMG predict recovery in patients with acute unilateral or bilateral vocal fold paralysis? (2) Do LEMG findings change clinical management in these individuals? A systematic review was performed using American Academy of Neurology criteria for rating of diagnostic accuracy. Results: Active voluntary motor unit potential recruitment and presence of polyphasic motor unit potentials within the first 6 months after lesion onset predicted recovery. Positive sharp waves and/or fibrillation potentials did not predict outcome. The presence of electrical synkinesis may decrease the likelihood of recovery, based on 1 published study. LEMG altered clinical management by changing the initial diagnosis from RLN in 48% of cases. Cricoarytenoid fixation and superior laryngeal neuropathy were the most common other diagnoses observed. Conclusions: If prognostic information is required in a patient with vocal fold paralysis that is more than 4 weeks and less than 6 months in duration, then LEMG should be performed. LEMG may be performed to clarify treatment decisions for vocal fold immobility that is presumed to be caused by RLN. Muscle Nerve 53 : 850–855, 2016